OP0306 CD11C-SPECIFIC ABLATION OF SHP1 INDUCES AUTOIMMUNE SIALADENITIS SIMILAR TO SJÖGREN'S SYNDROME. (2nd June 2020) - Kinoshita, M.; Kaneko, Y.; Watanabe, M.; Imai, Y.; Shrestha, S.; Suwa, J.; Ohishi, Y.; Hamatani, H.; Nakasatomi, M.; Sakairi, T.; Ikeuchi, H.; Nojima, Y.; et al.
Abstract : Background: Dendritic cells (DCs) play important roles in inducing immune response as well as maintaining immune tolerance. Src homology 2 domain-containing protein tyrosine phosphatase-1 (Shp1) is a negative regulator of signaling in hematopoietic cells and is expressed in a variety of immune cells including DCs. Shp1 homozygous mutant mice (motheaten mice) develop multiple immunological abnormalities and they die around four weeks after birth because of severe pneumonitis. Motheaten mice produce large amounts of autoantibodies, and besides, B-1a cells, a distinct B cell subset, which are an important source of autoantibodies increase in these mice. The functional abnormality of DCs in motheaten mice has not been characterized, but DCs and macrophages increase in various organs of motheaten mice. To analyze the function of Shp1 in DCs, we generated Shp1 conditional knockout mice (Shp1 CKO) in which Shp1 gene is specifically depleted in CD11c + cells. We found that aged shp1 CKO developed autoimmune glomerulonephritis. We also found that they developed severe tubulointerstitial nephritis (TIN) at the age of 40 weeks, which is characterized by the infiltration of CD11c + and F4/80 + cells. CD4 + T cells from Shp1 CKO produce much more amount of IFNγ. Collectively, Shp1 in DCs acts as a key regulatory molecule to protect against autoimmunity. Objectives: We analyzed salivary glands of CKO to confirm whether they have autoimmune sialadenitis because TIN is known to be the most common renal manifestations of Sjögren's syndrome in human. Methods: Shp1 CKO are generated by crossing a mouse line carrying floxed Shp1 allele to mice expressing Cre recombinase under the control of the CD11c promoter. Sex- and age-matched Ptpn6 fl/fl littermates without Cre gene were studied as controls. We analyzed secretory function of the salivary glands in response to pilocarpine stimulation in Shp1 CKO at the age of 40 weeks or older. We then performed histological examination of salivary glands (submandibular glands and sublingual glands) with light-microscopy and immunohistochemical staining. The mononuclear cells prepared from the salivary glands were analyzed by flow cytometry (FCM). We also quantified anti-SSA/Ro60 antibodies and anti-SSB/LA antibodies by ELISA. Results: Shp1 CKO secreted less saliva flow compared to control mice by pilocarpine stimulation. Histological study showed Shp1 CKO exhibited massive infiltration of inflammatory cells in salivary glands associated with periductal foci and periductal fibrosis. Most of infiltrated cells were stained by anti- CD4 or B220 mAbs. FCM revealed that B cells increased in the salivary glands of Shp1 CKO. In addition, B-1a cells also increased in the salivary glands of the mice. The levels of anti-SSA/Ro60 antibodies and anti-SSB/LA antibodies were increased in Shp1 CKO. Conclusion: CD11c-specific ablation of Shp1 induces the ectopic generation of lymphoid structure in salivary glands and impairment of salivary secretion. Autoantibody profile in Shp1 CKO resembled that in human Sjögren's syndrome. Our findings suggest that aged Shp1 CKO have the potential to become a new mouse model for the analysis of Sjögren's syndrome. References: [1]Green C. M. et al. J Heredity. 1975; 250-258. [2]Kaneko T. et al. J Immunology. 2012; 5397-540. [3]Watanabe M. et al. Biochem Biophys Rep. in press. Disclosure of Interests: Masato Kinoshita: None declared, Yoriaki Kaneko Grant/research support from: CHUGAI PHARMACEUTICAL CO., LTD. Astellas Pharma Inc. b, Speakers bureau: CHUGAI PHARMACEUTICAL CO., LTD. Astellas Pharma Inc., Mitsuharu Watanabe: None declared, Yoichi Imai: None declared, Shreya Shrestha: None declared, Junya Suwa: None declared, Yuko Ohishi: None declared, Hiroko Hamatani: None declared, Masao Nakasatomi: None declared, Toru Sakairi: None declared, Hidekazu Ikeuchi Speakers bureau: CHUGAI PHARMACEUTICAL CO., LTD. Astellas Pharma Inc., Yoshihisa Nojima: None declared, Keiju Hiromura Grant/research support from: CHUGAI PHARMACEUTICAL CO., LTD. Astellas Pharma Inc., Speakers bureau: CHUGAI PHARMACEUTICAL CO., LTD. Astellas Pharma Inc.